Pain management in patients with rheumatoid arthritis. Issue 5 (15th May 2015) - Durham, Catherine O.; Fowler, Terri; Donato, AnneMarie; Smith, Whitney; Jensen, Elizabeth
<x xml:space="preserve">Abstract</x> Abstract: Rheumatoid arthritis (RA) is one of the most common inflammatory conditions in the United States affecting approximately 1 million adults. This article briefly reviews the evidence-based diagnosis of RA, mainstays of treatment to prevent joint destruction, and pain management.